Analysis of Cash Flow Shenanigans at PT Cakra Mineral Tbk - Natalis Christian; Karen Karen; Kelvina Yenanda; Vinvin Evelyn (Lafadz Jaya Publisher, 2023)
The cash flow statement presents the company's cash flows are divided into 3 categories, which is operating, investing and financing activities. The purpose of this research is to examine and analyze cash flow shenanigans at PT Cakra Mineral Tbk in 2014-2016. This research is in the form of a case study involving fraud cases committed by PT Cakra Mineral Tbk. In detecting and analyzing fraud in company financial statements, this study uses secondary data that can be obtained from the IDX website or company website. The results of the analysis show that there are indications that PT Cakra Mineral Tbk has fake cash flows because the company consolidated its financial statements with two companies that had not been legally acquired. This can lead to an increase in revenue as shown in the 2016 report. This significant increase in sales can also be caused by an acquisition agreement that has beautified its financial statements. Apart from that, this company can also be said to be a red flag of selling receivables due to a drastic decrease of receivables in 2016, while in previous years there was no decrease as much. Based on the results of the analysis, this fraud has caused losses to various parties.